Earnings Management and Income Distribution Around a 'Breakeven or Near Breakeven Surplus' Benchmark with the Public Sector - Pilcher, Robyn; Van der Zahn, J-L.W. (Accounting and Finance Association of Australia and New Zealand, 2008)
An examination of an operating performance and earnings management linkage within the public sector is both topical and timely as government institutions and enterprises worldwide are increasing facing greater political and stakeholder scrutiny to improve financial performance and accountability. Empirical analysis on this issue, however, is limited and remains an open question. Our primary objectives addressing the gap in the literature are threefold. First, we examine the distribution of reported net income of NSW local governments to determine any evidence of any discontinuous dispersion around the „breakeven or near breakeven surplus‟ benchmark. Second, we examine if earnings management practices of local governments reporting deficits, low surpluses or high surpluses differ. Finally, we set out to determine if demographical features explain variations in earnings management, and if influence of such features on earnings management differs across groups of local governments reporting deficits, low surpluses and high surpluses.Our analysis is based on a sample of 411 observations for NSW local government covering a three fiscal year period. We find little evidence of kinks (or discontinuous) points in the income distribution implying a lack of any earnings management designed to avoid reporting net incomes close to zero. The level of discretionary accruals is found to vary between the three key net income sub-categories. Results, however, appear contrary to our proposition local governments seek to manage earnings upward or downward toward a „breakeven or near breakeven surplus‟ benchmark. Finally, we find little evidence of the association between demographical features and discretionary working capital accruals that also vary between the three net income sub-categories. Overall, our findings have important implications for officials at different levels of government and amongst key stakeholders. For example, our results suggest the dysfunctional use of discretionary accruals by NSW local governments could lead to the misallocation of key resources.